2003
DOI: 10.4049/jimmunol.170.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of a Specific Self-Peptide: Self-MHC Class II Complex Is Critical for Positive Selection of Thymocytes Expressing the D10 TCR

Abstract: We examined the specificity of positive and negative selection by using transgenic mice carrying a variant of the D10 TCR. We demonstrate that a point mutation at position 51 within the CDR2α segment significantly reduces the avidity of this TCR for its cognate ligand, but does not impact recognition of nonself MHC class II molecules. Although structural studies have suggested that this TCR site interacts with the MHC class II β-chain, the avidity of this TCR for its ligand and the function of the T cell can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Both D10 and L51S mice were bred onto a C␣ Ϫ/Ϫ background to ensure that no endogenous ␣-chains were used for pairing with the transgenic ␤-chain. In separate, but related, studies we now show that this mutation in the TCR that lowers its affinity to its specific MHC:peptide ligand reduces positive selection of immature T cells in the thymus (42) and results in the appearance of mature memory phenotype CD4 T cells in the periphery. In this study we show that the memory phenotype of these CD4 T cells does not translate into effector memory function.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Both D10 and L51S mice were bred onto a C␣ Ϫ/Ϫ background to ensure that no endogenous ␣-chains were used for pairing with the transgenic ␤-chain. In separate, but related, studies we now show that this mutation in the TCR that lowers its affinity to its specific MHC:peptide ligand reduces positive selection of immature T cells in the thymus (42) and results in the appearance of mature memory phenotype CD4 T cells in the periphery. In this study we show that the memory phenotype of these CD4 T cells does not translate into effector memory function.…”
mentioning
confidence: 73%
“…1C). This reduced number of CD4 T cells in the periphery is due to poor positive selection in the thymus (42).…”
Section: An Amino Acid Substitution From L To S At Position 51 Of Thementioning
confidence: 99%
“…In our model, we found that thymocytes exposed to IL-12-plus-IL-18 produce IFN-␥ that in turn can mediate IA-IE expression in cortical and medullary TEC. This is important considering that MHC class II expression by TEC is essential during negative and positive selection (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…cDNA clones for wild-type HLA-DMA and the mutant version of HLA-DMB were cloned into the pMCFR expression vector (21). The vectors were transfected by electro- poration into the B cell line CH27 (22). Stable clones were derived by selection with G418.…”
Section: Methodsmentioning
confidence: 99%